A numerical assessment of the effect of concatenating arbitrary uncoupled multicore fiber segments on intercore crosstalk in long-haul communication links - Rebola, J. L.; Cartaxo, A. V. T. (Photonics, 2024)
Random core dependent loss (CDL) has been shown to increase the direct average intercore crosstalk (ICXT) power in long-haul uncoupled multicore fiber (MCF) links. Longer links are composed of multiple MCF segments, and random CDL may arise on these links from manufacturing imperfections. During link implementation, other random effects may arise and enhance the ICXT power. In this work, the effect of concatenating MCF segments with random characteristics on the direct average ICXT power in long-haul links is assessed numerically by studying the influence of the randomness of segment length, coupling coefficient, and random CDL on the mean, standard deviation, relative spread, and excess kurtosis of the ICXT power. The numerical results show that the segment length randomness marginally affects the ICXT power. For 2000 km long links and a 6 dB maximum random variation of the coupling coefficients, the mean almost doubles and the standard deviation almost triples, relative to considering only random CDL. However, the effect of the coupling coefficients randomness on the relative spread and excess kurtosis is reduced, not affecting significantly the nearly Gaussian distribution of the direct average ICXT power and the excess of direct average ICXT power (less than a 0.26 dB increase relative to considering only random CDL).